충남 디스플레이산업 혁신네트워크의 인적요소 지원활동 분석 - 조진희(Jo, Jin Hee); 이재홍(Lee, Jae Hong); 황희연(Hwang, Hee Yeon) (국토계획, 2014)
세계화의 진전은 기업 간 경쟁시대에서 지역 간 경쟁시대를 유도하고 있다. 특히 초기투자 부담과 위험이 따르는 단독기업 중심의 산업정책은 클러스터를 통한 공동기술 및 사업 개발, 자금 및 위험 분담 등이 정책으로 전환되고 있다(정의동외 2인, 2007). 또한 최근의 산업이론은 지속적인 혁신과정과 경제적 성장을 가능하게 해주는 네트워킹과 그 속에서 행위자의 역할에 초점을 맞추고 있으며, 산업지역 내 주요 행위자 사이의 연계는 상생협력과 경쟁메커니즘을 창출・유지하기 위한 핵심요소로 평가되고 있다(국가균형발전위원회, 2005). 즉, 물리적 하부구조에서 기술혁신환경의 중요성을 강조해 온 클러스터 논의에서 혁신을 위한 네트워크 활동이 강조되어짐을 의미한다. 따라서 본 연구는 혁신을 구성하는 다양한 요소 가운데 기술혁신환경의 중요한 요소인 인적활동 네트워크의 협력구조에 대한 해석을 시도한다. 또한 k-core기법을 적용하여 인적요소 지원활동에 의해 형성되는 미시적 협력집단의 구조를 분석하고, 산업계 담당자를 대상으로 분석결과에 대한 심층인터뷰를 통해 정책적 함의를 도출하고자 한다. 이를 위해 본 연구는 2단계의 연구목표를 설정한다. 첫 째는 혁신네트워크의 인적요소 지원활동에 의해 형성되는 협력구조를 확인한다. 두 번째는 산업가치사슬과 연계하여 동질 혹은 유사한 혁신기관의 협력구조에서 나타나는 네트워크 군집현상의 구조적 특성을 확인하는 것을 본 연구의 목적으로 설정한다. This study pays attention to a human supporting activity in innovation network, an element for industrial innovation. This study aims at positively checking the innovation network structure of human element supporting activity formed in an industrial area. The survey and analysis for this were performed for 4 human element supporting activity factors such as research collaboration and joint research, manpower exchange, technology purchase and sale, and conference and seminar, for the display industry related institutions located in the Chungnam area. The study was carried out in 3 steps such as theory consideration, analysis system and analysis data establishment, and positive analysis and conclusion. The theory consideration step presented a concept of innovation network and network analysis and a theoretical basis of analysis system. As a result of centrality analysis, the introverted connection centrality was high in enterprises with funding power, and the extroverted connection centrality was high in metropolitan councils and their funded research centers playing a supporting role for enterprises. As a result of group structure analysis, 3 clustering groups were formed, and as a result of integration degree analysis for clustering groups, the clustering groups including various innovation institutions and value chain step institutions were high in network integration degree. In addition, it was confirmed that the spatial integration degree pursuant to the change of network integration degree has a positive correlation. KCI Citation Count: 0